2000
DOI: 10.1038/sj.onc.1203378
|View full text |Cite
|
Sign up to set email alerts
|

Non-activated p53 co-localizes with sites of transcription within both the nucleoplasm and the nucleolus

Abstract: The p53 tumour suppressor functions as a sensor of genotoxic stress and, once activated, induces cell growth arrest or apoptosis. The precise intranuclear localization of latent p53 protein in non-stressed cells is unknown. Such information is essential in order to understand how relatively few molecules of p53 can detect and respond to DNA damage. Here we present the ®rst detailed supramolecular localization of p53 in the nuclei of cells under normal conditions of growth. We show that soluble, non-bound p53 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 42 publications
(42 reference statements)
4
52
0
Order By: Relevance
“…Within the nucleus, p53 has been reported to be associated with at least three subnuclear compartments including the nucleolus, promyelocytic leukemia bodies and cajal bodies (Mogaki et al, 1993;Benninghoff et al, 1999;Rubbi and Milner, 2000;Horky et al, 2001;Klibanov et al, 2001;Wesierska-Gadek et al, 2002;Young et al, 2002;Zimber et al, 2004). Approximately half of nuclear p53 is soluble, whereas the remainder associates with nuclear structures (Zerrahn et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Within the nucleus, p53 has been reported to be associated with at least three subnuclear compartments including the nucleolus, promyelocytic leukemia bodies and cajal bodies (Mogaki et al, 1993;Benninghoff et al, 1999;Rubbi and Milner, 2000;Horky et al, 2001;Klibanov et al, 2001;Wesierska-Gadek et al, 2002;Young et al, 2002;Zimber et al, 2004). Approximately half of nuclear p53 is soluble, whereas the remainder associates with nuclear structures (Zerrahn et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has become increasingly clear that they actively participate in the apoptosis process. Non activated p53 significantly localizes to nucleoli and is believed to monitor sites of active transcriptional activity, 33 and UBF has been shown to be cleaved by caspases early during apoptosis. 34 It was demonstrated that UBF moves out of nucleoli during apoptosis whereas other nucleolar protein such as B23 stay within these structures.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a mechanism for regulating p53 function, potentially by physical sequestration of p53 in a cellular compartment that inhibits p53 function. Nucleolar accumulation of p53 has recently been shown (41,42). SMN can also accumulate within the nucleolus of adult neuronal cells and all fetal cell types (31, 32).…”
Section: Smn Complexes With P53 In Vivo and Inmentioning
confidence: 99%